2020
DOI: 10.3102/0162373720968558
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship Between Inclusion, Absenteeism, and Disciplinary Outcomes for Students With Disabilities

Abstract: Students with disabilities (SWDs) are more likely to be suspended or expelled than their general education peers and more likely to be chronically absent. This study uses 5 years of student-level data for all Michigan special education students to examine the relationship between educational setting, absenteeism, and disciplinary outcomes. Using within-student variation in an educational setting, I find that the degree of inclusion is associated with fewer disciplinary incidents and better attendance. However,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 68 publications
(92 reference statements)
0
2
0
Order By: Relevance
“…Students with disabilities experience exclusionary discipline at almost three times the rate of students without disabilities (Hurwitz et al, 2021) despite the provision of manifestation determination reviews (MDRs) for students with disabilities under Individuals with Disabilities Education Act (IDEA). This finding of an increased rate of exclusionary discipline experienced by students with disabilities has been echoed in the literature (e.g., Anderson, 2021;Green et al, 2019;Ryan & Goodram, 2013;Skiba et al, 2014;. These increased rates of exclusionary discipline appear to impact students with emotional and behavioral disorders more so than other disability categories (e.g., Blackwell et al, 2019;Bowman-Perrott et al, 2013;.…”
Section: Research-article2023mentioning
confidence: 84%
“…Students with disabilities experience exclusionary discipline at almost three times the rate of students without disabilities (Hurwitz et al, 2021) despite the provision of manifestation determination reviews (MDRs) for students with disabilities under Individuals with Disabilities Education Act (IDEA). This finding of an increased rate of exclusionary discipline experienced by students with disabilities has been echoed in the literature (e.g., Anderson, 2021;Green et al, 2019;Ryan & Goodram, 2013;Skiba et al, 2014;. These increased rates of exclusionary discipline appear to impact students with emotional and behavioral disorders more so than other disability categories (e.g., Blackwell et al, 2019;Bowman-Perrott et al, 2013;.…”
Section: Research-article2023mentioning
confidence: 84%
“…A study from the United States analyzing school absence data for special education students (K. P. Anderson, 2021) reported that 19% of children on the autism spectrum were missing at least 10% of school days/year, compared to 14% of students in general education.…”
Section: Resultsmentioning
confidence: 99%
“…Recent population-based studies on neurodevelopmental conditions suggest elevated levels of school absenteeism in autistic children compared with their peers in the United States and the United Kingdom (K. P. Anderson, 2021; John et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In recent years, many school districts and states have sought to reduce exclusionary discipline such as out-of-school suspension (OSS) and expulsion due to growing awareness of the academic and life consequences of excluding students from school (e.g., Anderson, Ritter, & Zamarro, 2019; Bacher-Hicks et al, 2019; Chu & Ready, 2018; Davison et al, 2021; Fabelo et al, 2011; Nicholson-Crotty et al, 2009; Wolf & Kupchik, 2017), as well as concern about disproportionalities in exclusionary discipline by race and disability status (e.g., Anderson, 2021; Anderson & Ritter, 2017; Liu et al, 2021; Losen et al, 2015; Shi & Zhu, 2021; Skiba et al, 2011; Skiba et al, 2014; Sullivan et al, 2013; Vincent et al, 2012).…”
Section: Introductionmentioning
confidence: 99%